Effect of Timber Harvesting Techniques and Slopes on Soil Respiration of Young and Mature Black Pine Stands in Northwestern Türkiye - Cigdem Ozer Genc; Temel Sariyildiz; Burak Aricak (BioResources)
Releases of CO2 from forest soils was studied relative to different timber harvesting techniques, slope classes, and stand age. Three timber harvesting techniques (suspended skidding (SS), skidding by using a skidding cone (SC), and cable-pulling (CP)) were used in young and mature black pine stands at three different slopes (0 to 20% - S1, 20% to 33% - S2, and > 33% - S3). Soil respiration measurements were carried out at five-day intervals (1st, 5th, and 10th day) and 6 months later after the timber harvesting techniques. The soil respiration increased on the first day, decreased on the 5th and 10th days, and reached its lowest level on the 6th month. The SC technique in the young stands showed the highest soil respiration value on the slopes indicating that the cone placed on the head of the log during the skidding operations does not deform the soil. In the mature stands, all timber harvesting techniques and the undisturbed sites showed lower values than in the young stands on the S1. On the S2, mean value was higher in the mature stands. In contrast to the young stands, the undisturbed stands had the highest soil respiration.